Relationship between corporate governance mechanisms and earnings management in Malaysian government linked companies (GLCs) - Deneskumar s/o Krishnan; Rubeni d/o Sarawanabawan; Shavinder Kaur d/o Mahinder Singh; Thiviya d/o Selvamani (2025)
HD2741.D46 2017